2021
DOI: 10.3390/microorganisms9081559
|View full text |Cite
|
Sign up to set email alerts
|

Culture Degeneration Reduces Sex-Related Gene Expression, Alters Metabolite Production and Reduces Insect Pathogenic Response in Cordyceps militaris

Abstract: Cordyceps militaris is an entomopathogenic ascomycete, known primarily for infecting lepidopteran larval (caterpillars) and pupal hosts. Cordycepin, a secondary metabolite produced by this fungus has anti-inflammatory properties and other pharmacological activities. However, little is known about the biological role of this adenosine derivate and its stabilising compound pentostatin in the context of insect infection the life cycle of C. militaris. During repeated subcultivation under laboratory conditions a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…However, a highly excessive number of MAT1-2 spores can cause degeneration (Figure 3). A recent comparative analysis with quantitative real-time PCR also indicated that the expression of the MAT1-2-1 gene in a degenerated C. militaris strain was significantly higher than in its parental strain [28]. Based on this information and our results, we suggest that the abundance of the MAT1-1 monokaryotic spores in the mating combinations can support the stability of the fruiting body formation in the heterokaryotic C. militaris strains.…”
Section: Preserving the Monokaryotic Isolates Separately Before Matin...supporting
confidence: 78%
“…However, a highly excessive number of MAT1-2 spores can cause degeneration (Figure 3). A recent comparative analysis with quantitative real-time PCR also indicated that the expression of the MAT1-2-1 gene in a degenerated C. militaris strain was significantly higher than in its parental strain [28]. Based on this information and our results, we suggest that the abundance of the MAT1-1 monokaryotic spores in the mating combinations can support the stability of the fruiting body formation in the heterokaryotic C. militaris strains.…”
Section: Preserving the Monokaryotic Isolates Separately Before Matin...supporting
confidence: 78%
“…We compared their radical expansion after 12 days of culture on PDA plates and found that the degenerate strain reduced radical expansion by approximately 50% compared to the wild type strain. While Wellhan et al (2021) reported nonsignificantly slower radical growth rates in the degenerate strain, they did not show its ability to form fruiting bodies, so it is unclear whether the “degenerate” strain is truly degenerate (25). Our study revealed that the degenerated strain showed a significantly higher conidia density than the wild-type strain, which contradicts the findings of Meiyu et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps militaris, for example, is commercially cultivated as a pharmaceutical and food resource and frequently degenerates through subculture and storage. Next to the degeneration of fruiting body formation, secondary metabolite production is reduced, leading to high economic losses (Xiong et al 2013;Sun et al 2017;Yin et al 2017;Lou et al 2019;Wellham et al 2021). Their ability to sexually reproduce adds another layer of complexity, which might be the reason why this is not reviewed in the literature.…”
Section: Introductionmentioning
confidence: 99%